2021
DOI: 10.33546/bnj.1276
|View full text |Cite
|
Sign up to set email alerts
|

Stress, adversity quotient, and health behaviors of undergraduate students in a Thai university during COVID-19 outbreak

Abstract: Background: University students are an essential human resource for national development. Thus, it is important to study the stress, adversity quotient, and health behaviors of these students during the COVID-19 pandemic.Objective: This study aimed to identify stress, adversity quotient, and health behaviors and examine the relationship between these factors in undergraduate students during the COVID-19 outbreak.Methods: The current study was a quantitative study with a cross-sectional design. A total of 416 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“… 1 , 2 Due to the virulence and mutations of the virus causing such disease (severe acute respiratory syndrome coronavirus 2), the number of human infections is continuing to increase, and the pathogenesis is more severe worldwide than in the first wave. 3 Worldometers 4 reported that as of July 11, 2021, there have been 187,632,756 cases of COVID-19 infection and 4,049,071 COVID-19 deaths. The World Health Organization also reports the new cases of infection and deaths around the world, and the data show that COVID-19 affects all age groups and especially people who have high health risks or a weak immune system.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Due to the virulence and mutations of the virus causing such disease (severe acute respiratory syndrome coronavirus 2), the number of human infections is continuing to increase, and the pathogenesis is more severe worldwide than in the first wave. 3 Worldometers 4 reported that as of July 11, 2021, there have been 187,632,756 cases of COVID-19 infection and 4,049,071 COVID-19 deaths. The World Health Organization also reports the new cases of infection and deaths around the world, and the data show that COVID-19 affects all age groups and especially people who have high health risks or a weak immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the new cases spread rapidly through diverse communities. [1][2][3][4] Worldometer 5 reported that as of October 3, 2021, the total prevalence of global cases is 235 million and there have been 4.81 million deaths. As mentioned earlier, the healthcare providers, who are working as the frontliners during the pandemic, are perceived to be overwhelmed and experiencing burnout, even posttraumatic stress disorder (PTSD), from the deluge of COVID-19 cases they have been handling.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, media campaigns and home visits by public health volunteers and public health workers have resulted in the successful prevention of COVID-19 to a large extent. 13 Nevertheless, elderly people continue to be a high-risk group. 4 In the past, most elderly people have received health promotion information from healthcare professionals during physician visits, elderly club activities, and routine home visits.…”
Section: Introductionmentioning
confidence: 99%